PENGARUH WAKTU PELINDIAN PADA PROSES PEMURNIAN SILIKON TINGKAT METALURGI MENGGUNAKAN LARUTAN HCl - Adjiantoro, Bintang; Mabruri, Efendi (Jurnal Metalurgi, 2012)
EFFECT OF LEACHING TIME ON PURIFICATION PROCESS OF METALLURGICAL GRADE SILICON BY USING ACID SOLUTION. The purification process of metallurgical grade silicon (MG-Si) using acid leaching method at a concentration of 2.45 mol/L HCl was performed by varying the leaching time at boiling temperature ( ±100 °C) and with mechanical stirring. The results showed that the leaching process of MG-Si with HCl can be used to eliminate the element of metal impurities. The extraction efficiency of impurity elements contained in the MG-Si by HCl dissolution is 99.996 % for Al, 98.247 % for Ti and 98.491 % for Fe at leaching time of 120 hours. Whereas the leaching efficiency of HCl solution on the impurities using mechanical stirring is 99.04 %.